Asymmetric competition among nation states: A differential game approach - Yutao Han; Patrice Pieretti; Skerdilajda Zanaj; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
This paper analyzes the impact of foreign investments on a small country's economy in the context of international competition. To that end, we model tax and infrastructure competition within a differential game framework between two unequally sized countries. The model accounts for the widely recognized characteristic that small states are more flexible in their political decision making than larger countries. However, we also acknowledge that small size is associated with limited institutional capacity in the provision of public goods. The model shows that the long-term outcome of international competition crucially depends on the degree of capital mobility. In particular, we show that flexibility mitigates against - but does not eliminate - the likelihood of collapse in a small economy. Finally, we note that the beneficial effect of flexibility in a small state increases with its inefficiency in providing public infrastructure and with the degree of international openness.
urn:nbn:de:0070-pub-26717074
Keywords: H25; H73; O30; O43; 330; Tax/Infrastructure competition; Open-loop/Markovian strategies; Differential games; Steuerwettbewerb; Infrastruktur; Standortwettbewerb; Spieltheorie; Landesgröße; Theorie